Analysis of the Instability Phenomena Caused by Steam in High-Pressure Turbines - Paolo Pennacchi; Andrea Vania (Shock and Vibration)
Instability phenomena in steam turbines may happen as a consequence of certain characteristics of the steam flow as well as of the mechanical and geometrical properties of the seals. This phenomenon can be modeled and the raise of the steam flow and pressure causes the increase of the cross coupled coefficients used to model the seal stiffness. As a consequence, the eigenvalues and eigenmodes of the mathematical model of the machine change. The real part of the eigenvalue associated with the first flexural normal mode of the turbine shaft may become positive causing the conditions for unstable vibrations. The original contribution of the paper is the application of a model-based analysis of the dynamic behavior of a large power unit, affected by steam-whirl instability phenomena. The model proposed by the authors allows studying successfully the experimental case. The threshold level of the steam flow that causes instability conditions is analyzed and used to define the stability margin of the power unit.